Patrons and adversaries : nobles and villagers in Italian politics, 1640-1760 - Castiglione, Caroline (Oxford University Press, 2005)
Four generations of the aristocratic Barberini family and its "vassals", clashed over how the early modern Roman countryside should be governed. Villagers sometimes cultivated noble interference, but they frequently resisted it through the strategies of adversarial literacy, political ways of reading and writing that challenged noble hegemony in the village.